NEED ASSESSMENT DALAM DESAIN PEMBELAJARAN STRATEGI KELOMPOK-KARYOTIP PADA MATA KULIAH GENETIKA - Andi Faridah Arsal; Hartati; St. Fatmah Hiola (Universitas Negeri Makassar, 2023)
A Needs assessment is the first step that must be done in learning design activities. Needs assessment Analysis is done when facing problems in a lesson. The problems that are commonly encountered in learning Genetics courses are several scientific terms that are similar to one another and are considered difficult by most students. This has an impact on students' conceptual and factual understanding is low. Through the Needs Assessment instrument in the form of a questionnaire survey for lecturers and students, as well as observations identified problems in order to determine the right action, so that the learning design that will be carried out is the best solution. The survey results obtained are summarized and concluded as problem identification and then analyzed to find the right solution. The solution to the identification results obtained is learning the Karyotype Group Strategy, namely the first; class organization based on the shape of the grouping of chromosomes. Second; learning begins with forming groups or organizing classes, because at the same time it is a form of simulation of the core material of learning Genetics.